An Exploratory Study of Factors Influencing IT Project Initiation Decisions - Wut Yi, Htike Htike (Auckland University of Technology, 2012)
Information technology, information systems and applications have become key survival factors in modern organisations. Technology can transform and redefine organisations and the way they operate. As the power of information technology (IT) intensifies and organisations work to exploit the full capacity of IT, the role of IT management in those organisations becomes more and more important. This importance is reinforced by the increasing pervasiveness of IT along with highly competitive operating contexts. As IT initiatives are generally implemented via projects, the management of IT projects has come under increasing scrutiny. IT projects continue to fail; as a result, while research in IT project management has grown, many challenges for research and practice remain. There have been many studies of the IT project management context; however, very few have considered project initiation decisions. The primary intent of this research is therefore to investigate IT projects particularly in terms of their initiation. As these projects originate from decisions made by management, it is important to understand the drivers of these decisions. Therefore, the objective of this research is to explore the influencing factors in IT project decisions during their initiation. A combination of semi-structured interviews and the repertory grid data collection and analysis method was employed to investigate the motivating factors and primary drivers that influence individual IT Managers’ project initiation decisions. Eighteen participants representing six medium and large organisations were interviewed. A total of forty-nine IT projects were identified by these eighteen managers. A rich data set was collected and in-depth analysis was conducted. The results showed that there are multiple underlying reasons for the decisions made at this early stage and that there are some common patterns of decision drivers among the interviewed IT Managers. For instance, most projects are still motivated by a desire to achieve efficiencies or cost savings, their potential tends to be assessed using cost benfit analysis, and packaged software solutions along with consultancy services are widely employed in solution development and delivery. Drawing on the results as well as prior research, an ‘IT Project Pre-Initiation Decision Framework’ is proposed to assist IT Managers and others in their evaluation of rationales during the preliminary project initiation decision-making process. This multidimensional matrix evaluative framework is intended to assist IT Managers in ensuring the cogency of rationales with an ability to make objective appraisals. In order to justify the proposed approach as a universal evaluative framework, it is necessary to conduct in-depth and longitudinal case studies from different perspectives. Future research is also needed in identifying to what extent project initiation decision(s) might lead to successful or unsuccessful project outcomes.
Keywords: IT Project Management; IT Project Initiation; IT Project Decisions